Ecological responses of periphyton dry mass and epilithic diatom community structure for different atrazine and temperature scenarios - Chakandinakira, Adroit Takudzwa; Mwedzi, Tongayi; Tarakini, Tawanda; Bere, Taurai (Water SA, 2019)
Climate change–induced temperature increase may influence the ecotoxicity of agricultural herbicides such as atrazine and consequently negatively impact aquatic biota. The objective of this study was to assess the effects of increased temperature on the ecotoxicity of atrazine to diatom community structure and stream periphyton load using laboratory microcosm experiments. A natural periphyton community from the Mukwadzi River, Zimbabwe, was inoculated into nine experimental systems containing clean glass substrates for periphyton colonisation. Communities were exposed to 0 µg∙L-1 (control), 15 µg∙L-1 and 200 µg∙L-1 atrazine concentrations at 3 temperature levels of 26°C, 28°C and 30°C. Periphyton dry weight and community taxonomic composition were analysed on samples collected after 1, 2 and 3 weeks of colonisation. A linear mixed-effects model was used to analyse the main and interactive effects of atrazine and temperature on dry mass, species diversity, evenness and richness. Temperature and atrazine had significant additive effects on species diversity, richness and dry mass. As temperature increased, diatom species composition shifted from heat-sensitive species such as Achnanthidium affine to heat-tolerant species such as Achnanthidium exiguum and Epithemia adnata. Increasing temperature in aquatic environments contaminated with atrazine results in sensitive and temperature-intolerant diatoms being eliminated from periphyton communities. Climate change will exacerbate effects of atrazine on periphyton dry mass and diatom community structure.